Advancements in metabolic engineering: unlocking the potential of key organic acids for sustainable industrial applications - Wang, Tengfei; Xue, Han; Liu, Hongling; Yuan, Haibo; Huang, Di; Jiang, Yi (Frontiers in Bioengineering and Biotechnology, 2025)
This review explores the advancements, application potential, and challenges of microbial metabolic engineering strategies for sustainable organic acid production. By integrating gene editing, pathway reconstruction, and dynamic regulation, microbial platforms have achieved enhanced biosynthesis of key organic acids such as pyruvate, lactic acid, and succinic acid. Strategies including by-product pathway knockout, key enzyme overexpression, and improved CO2 fixation have contributed to higher production efficiency. Additionally, utilizing non-food biomass sources, such as lignocellulose, algal feedstocks, and industrial waste, has reduced reliance on conventional carbon sources, supporting sustainability goals. However, challenges remain in substrate inhibition, purification complexity, and metabolic flux imbalances. Addressing these requires omics-driven metabolic optimization, stress-resistant strain development, and biorefinery integration. Future research should focus on system-level design to enhance cost-effectiveness and sustainability, advancing industrial bio-manufacturing of organic acids.